Evaluation and management of orthostatic headache in hypermobility disorders - Fermo, Olga P. (Frontiers in Neurology, 2023)
Headache is a frequent symptom among patients with hypermobility spectrum disorders. This mini review focuses specifically on a challenging aspect of headache evaluation in all patients, but especially those with hypermobility – the orthostatic headache. While the differential for an orthostatic headache is overall limited, patients with hypermobility disorders have risk factors for all of the most commonly encountered orthostatic headache disorders. The most common conditions to produce orthostatic headaches are discussed – spontaneous intracranial hypotension, cervicogenic headache, and postural orthostatic tachycardia syndrome. Less common etiologies of orthostatic headache pertinent to any patient are presented in table format.